An Analysis of Translation Strategies of Tootsie’s Vocabulary from Thai into English: A Case Study of a TV Series, ‘Diary Tootsies the Series’ - Akkapong Pakjan; Kanokwan Kongpakdee; Supawadee Chookerd; Thassanee Thasrabiab (Journal of Communication in Scientific Inquiry (JCSI), 2024)
The study examined the strategies used in translating the Thai TV series, ‘Diary Tootsies the Series Season 1 and 2’ written and directed by Piyachart Thongaum. Employing Baker’s (1992) eight translation strategies of non-equivalence at the word level from Thai to English, the study identified the occurrences of each strategy, exemplified the techniques used, and described the translator’s intentions. Frequencies of occurrence were calculated to compare the use of translation strategies. The findings illustrated that seven of Baker’s (1992) translation strategies were used. The most frequently-employed translation strategy was Translation by a more general word, which accounted for 65 occurrences (36.72%) while the two least with 4 times (2.26 %) were Translation by using a loan word with or without explanation, and Translation by omission. The illustration-based translation, however, was not found. Furthermore, the study found 28 instances (15.82%) of literal translation, which was beyond Baker’s (1992) framework. The majority of gay terminologies according to findings, drew on existing Thai words before evolving into new meaning, usually relating to sexuality, resulting in some Thai words not being directly translated into English. Also, the greatest emphasis was placed on meaning while retaining the tootsieness in the target language was the least important factor. Evidently, gayness in the original text was diminished when translated into the target text. This study can assist translators in becoming aware of the unique characteristics of ladyboys’ dialogues and in employing different non-equivalence translation strategies to translate idiosyncratic words in ladyboys’ subtitle scripts in order to effectively convey their original meaning and flavor.’